Evaluation of Different Size of Broad Bed and Furrow for Surface Runoff and Soil Loss and Productivity of Groundnut (Arachis hypogea L.) under Rainfed Conditions of Gujarat, India - Vekariya, P. D.; Sanepara, D. P.; Limbasia, B. B.; Vora, V. D.; Hirpara, D. S. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
This chapter aims to study the effect of different size of broad bed and furrow on the surface runoff and soil loss and productivity of groundnut under rainfed conditions of Gujarat, India. The experiment was conducted during kharif season of 2003-04 to 2009-10 in medium black soil at Main Dry Farming Research Station, Targhadia (Rajkot), Gujarat, India. The experiment was set up using a randomized block design, with four different treatments in each of the three replications: Flat bed (45cm row spacing), broad bed (60 cm width) and furrow (30 cm) with 2 rows, broad bed (90 cm width) and furrow (45 cm) with 3 rows, broad bed (120 cm width) and furrow (60 cm) with 4 rows in runoff plot. On the basis of seven years pooled results, significantly highest pod (932kg ha-1) and haulm (3234 kg ha-1) yield under the broad bed (90 cm width) and furrow (45 cm) with 3 rows along with the minimum runoff (22.73%) and soil loss (483.40 kg/ha). Higher mean soil moisture content (25.87 % and 26.25 %) was recorded under the both soil depths 0-15 cm and 15-30 cm, respectively under the broad bed (90 cm width) and furrow (45 cm) with 3 rows, while lowest (24.24 % and 24.87 %) were recorded in the flat bed control (T1). The broad bed (90 cm width) and furrow (45 cm) with 3 rows also gave the highest net returns of Rs 23662/- with the benefit: cost ratio of 2.69. Total seasonal runoff from broad bed and furrow treatments was less than that from flat bed in every year of the study.